624. Significant Institutional Cost Savings from OPAT-Facilitated Discharge for Patients with Challenging Situations. (31st December 2020) - Alexander, Bryan; Bergman, Scott; Van Schooneveld, Trevor C; Cortes-Penfield, Nicolas W
Abstract: Background: Outpatient parenteral antimicrobial therapy (OPAT) programs are becoming a standard of care, however, program cost justification remains a challenge. One area of focus for institutions is facilitating timely discharge from the inpatient setting, and difficult to discharge patients are a group with which OPAT teams can be particularly impactful. Methods: This retrospective review identified patients intervened upon by the Nebraska Medicine OPAT team during the initial nine months after program implementation (4/1/19 - 12/31/19) for which routine efforts at discharge by primary teams had failed. Patients were planned for extended inpatient stays to complete the full duration of parenteral antibiotic therapy due to discharge issues given the therapy plan initially recommended by infectious disease consult teams. Outcomes evaluated included inpatient days of therapy avoided, associated financial metrics, and 30-day readmission rates. A matched cohort of patients with similar lengths-of-stay, infectious disease indications, medication use, and lack of major complications was identified to calculate a cost per inpatient day avoided. Results: A total of 17 difficult to discharge patients were intervened on by the OPAT team, leading to avoidance of 429 planned inpatient days. Based on calculation from internal matched cohort data, these OPAT interventions avoided an estimated 943, 000 in total inpatient costs. All-cause 30-day readmission was 24% (4 of 17 patients). Additionally, 15 of these therapy courses were shifted to hospital-associated outpatient infusion centers. Facilitation of enrollment for 11 of these patients in pharmaceutical manufacturer patient assistance programs resulted in replacement of outpatient medication totaling over 28, 000 in value. Reimbursements for two additional patients through either governmental or private insurance generated over 11, 000 in margin for the health system. Conclusion: Attention to complex discharge facilitation by OPAT programs can be a significant contribution to program cost justification, while also transitioning patients to therapy plans that lead to similar clinical outcomes when compared to the overall OPAT population. Disclosures: All Authors : No reported disclosures